Gestion Intégrale de la Qualité: univers des acteurs et contexte d'innovation - Harrisson, Denis (Labour / Le Travail, 1999)
Following a brief review of the concept of quality, the article analyzes the representations and practices of quality by managers and employees at four Quebec manufacturing plants - Comtel, Microcom, Primétal and Afcan. Each was involved in the transformational process of Total Quality Management. Concludes that there is a duality: either quality management reinforces the relationship of subordination to managerial authority, or, on the contrary, it is based on a negotiated agreement in which unions and workers make themselves heard.